2023
DOI: 10.3389/fimmu.2023.955369
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and IL-18BP in inflammatory dermatological diseases

Abstract: Interleukin (IL)-18, an interferon-γ inducer, belongs to the IL-1 family of pleiotropic pro-inflammatory factors, and IL-18 binding protein (IL-18BP) is a native antagonist of IL-18 in vivo, regulating its activity. Moreover, IL-18 exerts an influential function in host innate and adaptive immunity, and IL-18BP has elevated levels of interferon-γ in diverse cells, suggesting that IL-18BP is a negative feedback inhibitor of IL-18-mediated immunity. Similar to IL-1β, the IL-18 cytokine is produced as an indolent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 153 publications
0
15
0
1
Order By: Relevance
“…In the current clinical application, IL-17 inhibitors (e.g., sekukizumab, eccilizumab) have a good effect on psoriasis. IL-18 has also been found to be the initiator of the cytokine cascade, and the concentration of IL-18 in serum correlates with the severity index (PASI) of psoriasis [ 22 , 83 ]. Recent data suggest that IFN-γ can sustain the progression of skin diseases [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current clinical application, IL-17 inhibitors (e.g., sekukizumab, eccilizumab) have a good effect on psoriasis. IL-18 has also been found to be the initiator of the cytokine cascade, and the concentration of IL-18 in serum correlates with the severity index (PASI) of psoriasis [ 22 , 83 ]. Recent data suggest that IFN-γ can sustain the progression of skin diseases [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another antibody that binds to IL-13 is Tralokinumab, approved for the treatment of moderate to severe atopic dermatitis from the age of 12 years. Phase III studies of the drug used for 16 weeks showed an improvement in the clinical condition in over 75% of patients, including approximately 30% of patients after monotherapy and 56% of patients after combination therapy with a class 3 local glucocorticosteroid [64,70,71].…”
Section: Atopic Dermatitis Therapymentioning
confidence: 99%
“…This results in the production of pro-IL-18, which is subsequently released into the cytoplasm, where it undergoes activation. Eventually, IL-18 is transported to the extracellular space through cellular pores [44].…”
Section: Biology Of Il-18mentioning
confidence: 99%
“…Notably, IRAK1 and IRAK4 have been implicated in IL-18 signaling in Th1 and NK cells. These IRAKs further associate with the adaptor molecule TNF receptor-associated factor 6 (TRAF6), which in turn binds to the kinase TAK1 (transforming growth factor-b-activated kinase 1) [44]. TAK1 phosphorylates nuclear factor kappa B (NF-κB)-induced kinase (NIK), leading to NIK activation.…”
Section: Biology Of Il-18mentioning
confidence: 99%
See 1 more Smart Citation